Surgical Management of Congenital Unilateral Entropion in a Labrador Pup Using Modified Hotz-Celsus Technique - Udehiya, Rahul Kumar; Singh, Naresh Kumar; Mathew, Dayamon David (Biology, Engineering, Medicine and Science Reports)
A two-month-old male Labrador retriever pup was presented with a history of unilateral blepharospasm, and epiphora. The case was diagnosed with congenital unilateral entropion on physical and ophthalmic examination. The entropion condition was corrected surgically using modified Hotz-Celsus technique. Excellent recovery was observed, and no complication was recorded following treatment up to three monthspost surgery.
Keywords: Dog; Labrador; Epiphora; Entropion; HotzCelsus; Eye defects; Veterinary surgery